Inclusive and Effective Citizen Engagement : Participatory Budgeting - Makueni and West Pokot Counties - Omolo, Annette (World Bank, Washington, DC, 2018)
The introduction of citizen engagement into law is an idea that is gaining popularity around the world. New provisions in Kenya’s Constitution enshrine openness, accountability, and public participation as guiding principles for public financial management. Yet, translating participation laws into meaningful action on the ground is no simple task. Experience has shown that in the absence of commitment from leaders and citizens and without appropriate capacities and methodologies, public participation provisions may lead to simple tick the box exercises. With support from the Kenya participatory budgeting initiative (KPBI), and the commitment from West Pokot and Makueni county leaders, PB is being tested as a way to achieve more inclusive and effective citizen engagement processes while complying with national legal provisions. This report captures the experiences of Makueni and West Pokot counties.